The Role of Regulatory T Cells in Pulmonary Arterial Hypertension - Tian, Wen; Jiang, Shirley Y.; Jiang, Xinguo; Tamosiuniene, Rasa; Kim, Dongeon; Guan, Torrey; Arsalane, Siham; Pasupneti, Shravani; Voelkel, Norbert F.; Tang, Qizhi; Nicolls, Mark R. (Frontiers in Immunology, 2021)
Pulmonary arterial hypertension (PAH) is a chronic, incurable condition characterized by pulmonary vascular remodeling, perivascular inflammation, and right heart failure. Regulatory T cells (Tregs) stave off autoimmunity, and there is increasing evidence for their compromised activity in the inflammatory milieu of PAH. Abnormal Treg function is strongly correlated with a predisposition to PAH in animals and patients. Athymic Treg-depleted rats treated with SU5416, an agent causing pulmonary vascular injury, develop PAH, which is prevented by infusing missing CD4+CD25highFOXP3+ Tregs. Abnormal Treg activity may also explain why PAH disproportionately affects women more than men. This mini review focuses on the role of Tregs in PAH with a special view to sexual dimorphism and the future promise of Treg therapy.